Critical Role of the Interaction Gut Microbiota – Sympathetic Nervous System in the Regulation of Blood Pressure - Toral, Marta (Front Physiol, 2019)
Association between gut dysbiosis and neurogenic diseases, such as hypertension, has been described. The aim of this study was to investigate whether changes in the gut microbiota alter gut-brain interactions inducing changes in blood pressure (BP). Recipient normotensive Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR) were orally gavaged with donor fecal contents from SHR and WKY. We divided the animals into four groups: WKY transplanted with WKY microbiota (W-W), SHR with SHR (S-S), WKY with SHR (W-S) and SHR with WKY (S-W). Basal systolic BP (SBP) and diastolic BP (DBP) were reduced with no change in heart rate as a result of fecal microbiota transplantation (FMT) from WKY rats to SHR. Similarly, FMT from SHR to WKY increased basal SBP and DBP. Increases in both NADPH oxidase-driven reactive oxygen species production and proinflammatory cytokines in brain paraventricular nucleus linked to higher BP drop with pentolinium and plasmatic noradrenaline (NA) levels were found in the S-S group as compared to the W-W group. These parameters were reduced by FMT from WKY to SHR. Increased levels of pro-inflammatory cytokines, tyrosine hydroxylase mRNA levels and NA content in the proximal colon, whereas reduced mRNA levels of gap junction proteins, were found in the S-S group as compared to the W-W group. These changes were inhibited by FMT from WKY to SHR. According to our correlation analyses, the abundance of Blautia and Odoribacter showed a negative correlation with high SBP. In conclusion, in SHR gut microbiota is an important factor involved in BP control, at least in part, as consequence of its effect on neuroinflammation and the sympathetic nervous system activity.